2016
DOI: 10.2174/1874325001610010412
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Rachitic Genu Varus in Preschool Children in a Paediatric Health Institute in Egypt as One of the Developing Countries

Abstract: Background:Rachitic genu varus is one of the common conditions among the Egyptian children, despite the shinning sun of Egypt all the year.Purpose:The aim of the study was to estimate the incidence of rachitic genu varus among the Egyptian children, and to assess the risk factors contributing to it.Patients and Methods:This prospective study recruited a total of 250 consecutive children, being 130 males and 120 females, with rachitic bow legs or genu varus, between 2 - 4 years of age, together with 250 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In developing countries populated by high-risk ethnic groups, the failure, or non-existence, of vitamin D supplementation policies are main contributors to the rise in NR despite abundant sunshine [ 18 •, 45 47 ]. A recent study from Egypt reported a high incidence (13.1%) of rachitic genu varum in children aged 2–4 years [ 48 ]. The study reported the following risk factors to be associated with the development of NR: low socioeconomic status, insufficient family income, poor housing conditions, lack of sunlight exposure due to cultural practices, sole breast feeding and inadequate supplementation of vitamin D in children and pregnant women [ 48 ].…”
Section: Prevention and Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries populated by high-risk ethnic groups, the failure, or non-existence, of vitamin D supplementation policies are main contributors to the rise in NR despite abundant sunshine [ 18 •, 45 47 ]. A recent study from Egypt reported a high incidence (13.1%) of rachitic genu varum in children aged 2–4 years [ 48 ]. The study reported the following risk factors to be associated with the development of NR: low socioeconomic status, insufficient family income, poor housing conditions, lack of sunlight exposure due to cultural practices, sole breast feeding and inadequate supplementation of vitamin D in children and pregnant women [ 48 ].…”
Section: Prevention and Public Healthmentioning
confidence: 99%
“…A recent study from Egypt reported a high incidence (13.1%) of rachitic genu varum in children aged 2–4 years [ 48 ]. The study reported the following risk factors to be associated with the development of NR: low socioeconomic status, insufficient family income, poor housing conditions, lack of sunlight exposure due to cultural practices, sole breast feeding and inadequate supplementation of vitamin D in children and pregnant women [ 48 ].…”
Section: Prevention and Public Healthmentioning
confidence: 99%
“…Infancy is crucial for physical and cognitive development, and consequences can be avoided with attention to detail and awareness. Socioeconomic status and ability to obtain nutrients should also be considered during follow-up visits with infants, as nutritional rickets are more prevalent in lower-income environments [ 15 ]. In similar cases, multidisciplinary teams that include pediatricians, social workers, developmental and behavioral professionals, dietitians, hematologists, and endocrinologists should be included to ensure that the patient receives well-rounded care and that all aspects of the patient’s condition are managed appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some studies have reported other causes of nutritional rickets as well which include exclusive breastfeeding, no intake of supplements, use of cow's milk, mothers' poor nutritional status, and low socioeconomic status. 2,6,7 Although many studies have been conducted around the world to assess the risk factors of the nutritional rickets. 5,6,7 However, the risk factors of the nutritional rickets are under-studied in the Pakistan especially in the region of Rawalpindi.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 Although many studies have been conducted around the world to assess the risk factors of the nutritional rickets. 5,6,7 However, the risk factors of the nutritional rickets are under-studied in the Pakistan especially in the region of Rawalpindi. Therefore, this study aims to determine the risk factors of the nutritional rickets among the children in Holy Family Hospital of Rawalpindi.…”
Section: Introductionmentioning
confidence: 99%